A Note on Measuring Inclusive Growth and the Inclusiveness of Growth. (December 2017) - Mitra, Siddhartha
This article makes three basic contributions: (a) review an already existing measure of 'inclusive growth' derived from a measure of inclusiveness (an increase which is assumed to be associated with inclusive growth) and show that this is one among a class of an infinite number of possible measures; (b) identify two drawbacks associated with the class of measures of 'inclusive growth' mentioned in (a) and come up with a measure of inclusive growth which is not associated with one of these drawbacks and (c) propound a measure of inclusiveness of growth which allows the researcher the room to partition an income-ordered population into blocks so that he/she can concentrate on inter-block inequality in growth rates of per capita income and neglect intra-block inequality (note that the formulation of this measure allows the researcher to partition the population into blocks in any way which he/she wants to) in growth rates of individual incomes. JEL Classification: D30, D31